2017
DOI: 10.18632/oncotarget.22343
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification and molecular modeling characterization reveal a novelPROM1mutation in Stargardt4-like macular dystrophy

Abstract: Stargardt disease-4 (STGD4) is an autosomal dominant complex, genetically heterogeneous macular degeneration/dystrophy (MD) disorder. In this paper, we used targeted next generation sequencing and multiple molecular dynamics analyses to identify and characterize a disease-causing genetic variant in four generations of a Chinese family with STGD4-like MD. We found a novel heterozygous missense mutation, c.734T>C (p.L245P) in the PROM1 gene. Structurally, this mutation most likely impairs PROM1 protein stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 69 publications
1
22
1
Order By: Relevance
“…However, there are other clinically overlapping phenotypes, inherited both in autosomal dominant (ad) and recessive manner. Mutations in ELOVL4 and PROM1 lead to adSTGD-like phenotype and are known as STGD3 (MIM# 600 110) and STGD4 (MIM# 603786), respectively [7]. Similarly, heterozygous mutations in PRPH2, BEST1 and CRX, and bi-al-lelic variants in CRB1, RAB28, RDH11 and ROM1 are also known to cause STGD-like phenotypes [8 -13].…”
Section: Stgd-like Phenotypes Due To Variants In Other Genesmentioning
confidence: 99%
“…However, there are other clinically overlapping phenotypes, inherited both in autosomal dominant (ad) and recessive manner. Mutations in ELOVL4 and PROM1 lead to adSTGD-like phenotype and are known as STGD3 (MIM# 600 110) and STGD4 (MIM# 603786), respectively [7]. Similarly, heterozygous mutations in PRPH2, BEST1 and CRX, and bi-al-lelic variants in CRB1, RAB28, RDH11 and ROM1 are also known to cause STGD-like phenotypes [8 -13].…”
Section: Stgd-like Phenotypes Due To Variants In Other Genesmentioning
confidence: 99%
“…Prominin 1 ( PROM1 ; OMIM 604365 ) is commonly associated with cone-rod dystrophies. 1 However, throughout the literature, variations in PROM1 have been implicated in extremely varied and overlapping phenotypes that have been described as retinitis pigmentosa 2 , 3 , 4 , 5 , 6 , 7 , 8 ; retinitis pigmentosa with macular involvement 9 ; retinal dystrophy 8 ; cone-rod dystrophy 1 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ; bull’s-eye maculopathy 18 ; bull’s-eye maculopathy associated with rod, rod-cone, and macular dystrophy 19 ; Stargardt-like disease 20 , 21 , 22 , 23 ; macular dystrophy 24 ; and maculopathy with rod-cone dystrophy. 25 The age at onset, presenting symptoms, and severity of disease vary with sequence variations.…”
Section: Introductionmentioning
confidence: 99%
“…Missense and truncating mutations predominantly occurred within protein-coding sequences. Mutations in PROM1 were mainly missense and truncating mutations, including p.R373C, p.Y452fsX12, p. G614fsX626, and p.Q576X in the prominin domain, which are associated with human inherited diseases [95][96][97][98]. A recent study reported the identification of a point mutation at p.S281R (serine [S] changed to arginine [R] due the mutation of thymine [T] to guanine [G]) in the prominin domain of the PROM1 protein in 8/555 lung cancer patients [99].…”
Section: Discussionmentioning
confidence: 99%